Управління стратегіями комерціалізації інтелектуальних технологій - Маслак, Марія Володимирівна; Кобєлєва, Анна Валеріївна; Перерва, Петро Григорович (Національний технічний університет України "Київський політехнічний інститут ім. Ігоря Сікорського", 2023)
У статті розглянуто теоретико-методологічні засади формування та використання стратегій комерціалізації інтелектуальних технологій. Для практичного використання запропоновано шість базових стратегій, які знайшли найбільш широке використанні в практиці введенні в господарський обіг результатів інноваційної діяльності промислових підприємств. До таких стратегій авторами віднесено використання інтелектуальних технологій у власному виробництві; продаж прав власності; ліцензування; стратегічний альянс; спільне підприємство; створення виділеного підприємства. Розглянуто науково-методичну сутність кожної з пропонованих стратегій комерціалізації, сформовано блок-схему використання їх в практичній діяльності. Особливу увагу приділено розгляду стратегії комерціалізації інтелектуальних технологій з використанням виділених підприємств у формі спін-офф або спін-аут (spin-off / spin-out), що потребує окремого обговорення через відмінності у визначеннях.

The article examines the theoretical and methodological foundations of the formation and use of strategies for the commercialization of intellectual technologies. For practical use, six basic strategies are proposed, which have found the most widespread use in the practice of introducing the results of innovative activities of industrial enterprises into economic circulation. The scientific and methodological essence of each of the proposed commercialization strategies was considered, and a block diagram of their use in practical activity was formed. It has been proven that the actual use of the technology implies that the new technology or its elements will become a production resource at the developing enterprise. The sale of property rights involves the implementation of all stages of the commercialization process by another company that is sufficiently knowledgeable in this field. Licensing of ownership rights is characterized as granting permission to a third party to exercise ownership rights with due consideration. The commercialization strategy of a strategic alliance involves the presence of at least two companies that conduct joint research and development work. A joint venture is created for the purpose of combining the assets of enterprises. Special attention is paid to consideration of the strategy of commercialization of intellectual technologies using selected enterprises in the form of spin-off or spin-out (spin-off / spin-out), which requires a separate discussion due to differences in definitions. It is well-founded that spin-off enterprises are offspring enterprises that are separated from the parent enterprise for the purpose of independent development, development and introduction to the market of a new product or technology. In the spin-out strategy, the presence of a separate enterprise is not mandatory. The scientist agrees with the university on the terms of granting him, as a natural person, a license to use this property right, which he then, having concluded a license agreement with the university, provides in material form to the target allocated enterprise.
Management of commercialization strategies of intellectual technologies
Keywords: інтелектуальна технологія; комерціалізація; стратегія; ліцензування; спільне підприємство; стратегічний альянс; спін-офф; спін-аут; intellectual technology; commercialization; strategy; licensing; joint venture; strategic alliance; spin-off; spin-out